2004
DOI: 10.1113/jphysiol.2003.053249
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue‐related depression of the feline monosynaptic gastrocnemius–soleus reflex

Abstract: In decerebrate cats, changes in the monosynaptic reflex (MSR) of gastrocnemius-soleus (G-S) motoneurones were studied after fatiguing stimulation (FST) of the G-S muscles. Monosynaptic reflexes were evoked by stimulation of Ia fibres in the G-S nerve and recorded from a filament of ventral root (VR) L7. FST (intermittent 40 s(-1) stimulation for 10-12 min) was applied to the distal part of the cut VR S1. FST reduced MSR amplitudes to 0.64 +/- 0.04 (mean +/-s.e.m.) of the prefatigue values. The suppression rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
(84 reference statements)
2
24
0
3
Order By: Relevance
“…Second, group III and IV afferents may alter recurrent inhibition. In the cat, Renshaw cells tended to become less responsive (Windhorst et al, 1997;Kalezic et al, 2004), whereas in humans, recurrent inhibition was increased (Kukulka et al, 1986;Rossi et al, 2003). Finally, group III and IV muscle afferents may mediate changes in motoneuron afterhyperpolarization during fatigue; however, at least in the cat, this does not slow motoneuron discharge (Windhorst et al, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…Second, group III and IV afferents may alter recurrent inhibition. In the cat, Renshaw cells tended to become less responsive (Windhorst et al, 1997;Kalezic et al, 2004), whereas in humans, recurrent inhibition was increased (Kukulka et al, 1986;Rossi et al, 2003). Finally, group III and IV muscle afferents may mediate changes in motoneuron afterhyperpolarization during fatigue; however, at least in the cat, this does not slow motoneuron discharge (Windhorst et al, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…Many previous studies showed that supraspinal and spinal neural mechanisms account for the development of muscle fatigue 16,22,[24][25][26][27][28][29][30] . Decreases in descending inputs, Ia inputs from muscle spindles, and inhibitory inputs from group III and IV fibers to the MN *Correspondence: komiyama@faculty.chiba-u.jp during muscular fatigue have been proposed as potential mechanisms responsible for reducing MN excitability 22,[26][27][28]31) .…”
Section: Introductionmentioning
confidence: 99%
“…Under some experimental conditions (in experiments on animals with intact systems of supraspinal control and in tests on humans), the stretch reflex was facilitated under nociceptive influences [4][5][6][7][8][9], while under other conditions (in experiments on decerebrated animals) it was suppressed [10]. In addition, the effects of pain could depend on the site of its initiation with respect to the muscles directly involved in realization of the reflex.…”
Section: Introductionmentioning
confidence: 98%